Thermal respite for pedestrians in overheated urban environments – Introduction of a dynamic analysis of outdoor thermal comfort - Yu, Yichen; de Dear, Richard (Sustainable cities and society, 2022)
•Pedestrians’ thermal discomfort in daily commute is analogized to a capacitor.•The capacitor is fully charged when mean body temperature increment reaches 0.4°C.•A 0.7°C-minute decrement in mean skin temperature is needed for thermal respite.•A stretch of less severe heat exposure is more concerning than the hottest spots. Superimposition of global warming on urban heat islands is making outdoor cooling infrastructure critical to the maintenance of walkability of many cities. How to better arrange thermal respite (cooling infrastructure) to maximise pedestrians’ thermal comfort is still unclear. In this study, the thermal discomfort accumulating during episodic exercise in outdoor heat was compared to the charging of a capacitor. Skin temperature and core temperature responses were collected from a sample of human participants (n=24) who were exposed to bouts of simulated urban heat stress, while exercising on an ergometer at an intensity corresponding to a brisk walk. Thermal respite (wind and/or shade) was provided to the participants to discharge accumulated heat load after they reached a specific threshold of thermal discomfort. We found that the thermal discomfort capacitor of most participants (75%) became fully charged (‘pleasant’ → ‘intolerable’) after a 0.4 °C increment in mean body temperature, and its discharge required a 0.7 °C degree-minute decrement in mean skin temperature. The comfort capacitor analogy provides an estimate of the intensity and duration of cooling respite required by pedestrians during brief exposures to overheated urban climates. This provides guidance on engineering interventions to ameliorate overheated urban microclimates.